Security, Privacy, Trust Management and Performance Optimization of Blockchain Technology - Swarnkar M.; Bhadoria R.S.; Sharma N. (My University, 2025)
Blockchain is a developing technology which provides data storage, secure transactions and establishing trust in an open environment. Blockchain is widely implemented in cryptocurrency systems like Bitcoins, smart contracts, smart grids over IoT devices etc. Blockchain also has wide applications in healthcare, automobile industries, private and public sectors. This growing popularity of Blockchain is luring hackers to perform various cyber-attacks in order to detect vulnerabilities in the applied Blockchain system. A vulnerable block chain system is open for network breaches, data thefts and information manipulations. Therefore, it is important to design a Blockchain system with proper security, privacy and trust management. However, increasing security and privacy in Blockchain reduces its performance because security and privacy policies are overhead to the applied Blockchain system. Therefore, it is also important to optimize the performance of Blockchain system with proper implementation of security and privacy. This chapter discuss the current scenarios of security, privacy and trust issues in Blockchain. The chapter also discuss the proposed solutions regarding these issues. Further, the chapter discuss the performance analysis on increasing security and privacy in the Blockchain technology and proposed optimizations in the literature. This chapter is then conclude by providing few research directions for improving security, privacy and trust in Blockchain technology while keeping its performance optimized. © 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.